A Simple Model of Capital Market Equilibrium with Incomplete Information - Merton, Robert C. (Journal of Finance, 1987)
The sphere of modern financial economics encompases finance, micro investment theory and much of the economics of uncertainty.As is evident from its influence on other branches of economics including public finance, industrial organization and monetary theory, the boundaries of this sphere are both permeable and flexible.The complex interactions of time and uncertainty guarantee intellectual challenge and intrinsic excitement to the study of financial economics.Indeed, the mathematics of the subject contain some of the most interesting applications of probability and optimization theory.But for all its mathematical refinement, the research has nevertheless had a direct and significant influence on practice.It was not always thus.Thirty years ago, finance theory was little more than a collection of anecdotes, rules of thumb, and manipulations of accounting data with an almost exclusive focus on corporate financial management.There is no need in this meeting of the guild to recount the subsequent evolution from this conceptual potpourri to a rigorous economic theory subjected to systematic empirical examination.1 Nor is there a need III -2on this occasion to document the wide-ranging impact of the research on 2 finance practice.I simply note that the conjoining of intrinsic intellectual interest with extrinsic application is a prevailing theme of research in financial economics.The later stages of this successful evolution has however been marked by a substantial accumulation of empirical anomalies; discoveries of theoretical inconsistencies; and a well-founded concern about the statistical power of many of the test methodologies.3Finance, thus finds itself today in the seemingly-paradoxical position of having more questions and empirical puzzles than at the start of its modern development.To be sure, some of the empirical anomalies will eventually be shown to be mere statistical artifacts.However, just as surely, others will not be so easily dismissed.I see this new-found ignorance in finance as mostly of the useful type that reflects our "...express recognition of what is not yet known, but needs to be known in order to lay the foundation for still more knowledge." 5Anomalous empirical evidence has indeed stimulated wide-ranging research efforts to make explicit the theoretical and empirical limitations of the basic finance model with its frictionless markets, complete information, and rational, optimizing economic behavior.Although much has been done, this research line is far from closure.Some hold that the paradigm of rational and optimal behavior must be largely discarded if knowledge in finance is to significantly advance.Others believe that most of the important empirical anomalies surrounding the current theory can be resolved within that traditional paradigm.Whichever view emerges as the dominant theme in finance, our understanding of the subject promises to be greatly enriched by these research programs.